Penerapan Terapi Air Putih dan Kompres Hangat untuk Mengatasi Masalah Nyeri dan Gangguan Eliminasi Urin pada Pasien ISK di RSUD Ende : - Sekunda, Maria S.; Owa, Khrispina; Bai, Marieta K. S. (Poltekkes Kemenkes Kupang, 2025)
Urinary tract infection (UTI) is an infection caused by the growth of microorganisms in the urinary tract, which in normal conditions urine does not contain bacteria, viruses or other microorganisms. Urinary tract infections can occur in men and women of all ages. The purpose of this special study is that the author is able to apply the provision of drinking water therapy and warm compresses to overcome pain problems and changes in urine elimination patterns in patients with Mrs. SM with a medical diagnosis of UTI through a nursing process approach. The method used in the case study on Mrs. SM with UTI is a case study with a nursing process approach which was carried out on March 29-April 1, 2025 in the Internal Medicine Room of Ende Hospital. The results of the case study showed that the assessment data found in Mrs. S.M with UTI were weakness, pain in the waist, lower abdominal pain, pain that comes and goes and feels like being stabbed, painful urination, abdominal distension, bloating, grimacing face, BP: 110/80 mmHg, S: 38 0C, N: 94x/min, RR: 20x/min, urination comes out a little at a time. The nursing diagnosis raised in Mrs. S.M's case was pain and impaired urinary elimination. After implementation, the results obtained were that the problems of pain and impaired urinary elimination were resolved thanks to the cooperation of the patient, family and nurse. Nursing care carried out on Mrs. S.M's patient can run well thanks to the cooperation and support of the family. Therefore, it is expected that the patient will behave healthily by not holding back urine and consuming lots of water 8-10 glasses a day.